Ferrocene based chiral binuclear η6‐benzene‐Ru(II)‐phosphinite complexes: Synthesis, characterization and catalytic activity in asymmetric reduction of ketones. (29th June 2017) - Abdlhmed Al‐bayati, Yaser W.; Karakaş, Duygu Elma; Meriç, Nermin; Aydemir, Murat; Durap, Feyyaz; Baysal, Akın
Abstract : In the present study, a series of chiral C 2 ‐symmetric ferrocenyl based binuclear η 6 ‐benzene‐Ru(II) complexes bearing diphenylphosphinite and diisopropylphosphinite moieties have been synthesised. The new binuclear η 6 ‐benzene‐Ru(II)‐phosphinite complexes were characterised based on nuclear magnetic resonance ( 1 H, 13 C, 31 P–NMR), FT‐IR spectroscopy and elemental analysis. Then, these complexes have been screened as catalytic precursors in the transfer hydrogenation of acetophenone with 2‐propanol as both the hydrogen source and solvent in the presence of KOH. The corresponding optically active secondary alcohols were obtained in excellent conversion rates between 96 and 99% and moderate to good enantioselectivities (up to 78% ee ). The complex5 was the most efficient catalyst among the four new complexes investigated herein. Abstract : Chiral C2 ‐symmetric ferrocenyl based binuclear η 6 ‐benzene‐ruthenium(II) complexes bearing diphenylphosphinite and diisopropylphosphinite moieties have been synthesised. These complexes have been screened as catalytic precursors in the transfer hydrogenation of acetophenone with 2‐propanol in the presence of KOH. The corresponding optically active secondary alcohols were obtained in excellent conversion rates between 96 and 99 % and moderate to good enantioselectivities (up to 78% ee ).